“I’ve still got a lot of living left to do”: The Experience of Being Young and Living in Geriatric Residential Care - Chapple, Sarah (Critical Disability Discourses, 2012)
This article explores the perceptions of a 57-year-old woman with a physical disability who faces unique challenges while living in a residential care facility designed for a geriatric population. This pilot study used an exploratory, qualitative research methodology. The objectives of the study sought to answer the following question: How do working-age adults with physical disabilities experience living in a residential care facility designed for a geriatric population? The key themes arising from this study that will be discussed in this article include coping and adjustment, autonomy and choice, institutional culture and environment, relationships, and hope. Keywords: advocacy, coping, health care, hope, institutional care, relationships